Analysis of the Hadith on the Crime of Sariqah From the Perspective Of Criminal Law (Hudud) - Yasmin Raihanah Zaviril; Muhammad Amar Adly (AT-TAFAHUM: Journal of Law, 2021)
This study examines the concept of sariqah (theft) in Islamic criminal law (fiqh jinayah) from the perspective of the hadith, with particular emphasis on its classification as a hudud offense. Using a qualitative normative legal research method based on library research, the study analyzes primary sources, including the Qur'an and the hadith of the Prophet Muhammad (PBUH), as well as secondary sources such as classical and contemporary Islamic jurisprudence literature, scientific journals, and legal references. Data were collected through documentation techniques and analyzed descriptively and interpretively to identify the legal principles governing sariqah. The findings reveal that not every act of taking another person's property constitutes sariqah subject to hudud punishment. The application of the prescribed sanction requires the fulfillment of strict legal conditions, including the secret taking of property, the attainment of the minimum value (nisab), secure storage of the property (hirz), and the existence of criminal intent. The hadith play a fundamental role in clarifying these requirements and providing practical guidance for implementing the Qur'anic provisions on theft. The study also highlights the principle of syubhat (legal doubt), which prevents the enforcement of hudud penalties whenever uncertainty exists, reflecting the Islamic legal commitment to justice, fairness, and caution. Furthermore, differences among Islamic schools of thought concerning the interpretation of nisab and other legal conditions demonstrate the dynamic and flexible nature of Islamic jurisprudence. In the contemporary context, although hudud punishments remain the subject of legal and human rights debates, the underlying objectives of protecting property rights, preventing crime, and ensuring social justice continue to be highly relevant. The study concludes that a comprehensive and contextual understanding of the hadith is essential for accurately interpreting the concept of sariqah and appreciating the balance between legal certainty, justice, and public welfare embodied in Islamic criminal law.